Nurses' Attitude Toward Mental Illness in DhiQar, Iraq - Ahmed Hassan Hussein (Journal of Global Pharma Technology, 2018)
Stigma against mentally ill patients is highly prevalent among nurses. High rates authoritarianism and social restrictiveness, low rates of benevolence and community mental health ideology were noticed among nurses. Recommendations: These findings raise the importance of learning the nursing students and nurses about the stigma and the right attitudes towards mentally ill patients. Future studies need to be inclusive of larger samples and need to study other aspects of the problem like the etiology and impact on patients.Keywords: Nurses, Attitude, Mental illness